Epigenetic programming by early‐life stress: Evidence from human populations. Issue 3 (28th October 2014) - Vaiserman, A. M.; Trainor, Paul; Johnson, Randy
<x xml:space="preserve">Abstract</x> Background: A substantial body of experimental and epidemiological evidence has been accumulated suggesting that stressful events in early life including acute perinatal stress, maternal deprivation or separation, and variation in maternal care may lead to neuroendocrine perturbations thereby affecting reproductive performance, cognitive functions, and stress responses as well as the risk for infectious, cardio‐metabolic and psychiatric diseases in later life. Results: Findings from recent studies based on both genome‐wide and candidate gene approaches highlighted the importance of mechanisms that are involved in epigenetic regulation of gene expression, such as DNA methylation, histone modifications, and non‐coding RNAs, in the long‐term effects of exposure to stress in early life. Conclusions: This review is focused on the findings from human studies indicating the role of epigenetic mechanisms in the causal link between early‐life stress and later‐life health outcomes. Developmental Dynamics 244:254–265, 2015. © 2014 Wiley Periodicals, Inc.